Implementation of the business judgment rule doctrine under Law Number 16 of 2025 on the protection of the human rights of state-owned enterprise management in exercising their authority - Yogi Herlambang (Journal of Law, Administration, and Social Science, 2026)
State-Owned Enterprises (SOEs) possess a dual character as profit-oriented business entities and as instruments of the state in delivering public services. In law enforcement practice, the business losses incurred by SOEs are frequently equated with state financial losses, so that business decisions taken by directors in good faith are exposed to the risk of criminalization of policy. This condition may infringe the right to fair legal certainty and the right to a sense of security as guaranteed by Article 28D(1) and Article 28G(1) of the 1945 Constitution and Law Number 39 of 1999 on Human Rights. This study analyzes the implementation of the Business Judgment Rule (BJR) doctrine under Law Number 16 of 2025 concerning the Fourth Amendment to Law Number 19 of 2003 on SOEs and its relevance to the protection of the human rights of SOE management. The study employs a normative juridical method with statutory, conceptual, and case approaches, examining Constitutional Court Decisions Number 48 and 62/PUU-XI/2013, Constitutional Court Decision Number 25/PUU-XIV/2016, and the court decisions in the Hotasi Nababan, Karen Agustiawan, and Sofyan Basir cases. The findings show that the inconsistency of convictions in judicial practice reflects genuine legal uncertainty, whereas Law Number 16 of 2025 reinforces the BJR by affirming that the assets and losses of an SOE belong to and are the responsibility of the SOE as a legal entity. The rights to legal certainty and to a sense of security are derogable rights, yet they intersect with a non-derogable core, namely the principle of legality and recognition as a person before the law (Article 28I(1)), so that their limitation is subject to the requirements of Article 28J(2). Remedies for criminalization that violates human rights may be pursued through pretrial motions, acquittal or release from prosecution, judicial review, compensation and rehabilitation, and guarantees of non-repetition through legal reform. Accordingly, the BJR functions not only as an instrument of good corporate governance but also as an instrument for the protection of human rights, although Law Number 16 of 2025 still leaves disharmony with the state finance and anti-corruption law regimes that requires de lege ferenda reconstruction.   Kata kunci: Perlindungan HAM, Business Judgement Rule, BUMN, Kriminalisasi Kebijakan.